Polymorphism of Free Radicals Detoxification Genes GSTM1 and GSTT1 is Associated to Prostate Cancer Risk in men: Case Study in Benin - CAPO-CHICHI, D. CALLINICE (My University, 2023)
Most diseases including cancers are subsequent to the imbalance between oxidation and reduction in cells. Glutathione-s-transferases (GSTM1 and GSTT1) are cell detoxification enzymes which are involved in the conversion of free radicals derived from reduced oxygen (known to harm DNA) in oxidized molecules which are not harmful for the DNA. Cells with deficient GSTM1 or GSTT1 activity, have impaired cellular detoxification which exposed them to free radicals derived from environment, unhealthy nutrition, or some drugs, all of which can harm DNA and cause genomic instability leading to cancer. Hence, their implication in cancers affecting men in Benin was not investigated and needs to be addressed. The aim of this study is to assess the association between the loss of GSTM1 and GSTT1 and prostate cancer in Benin. Methods: GSTM1 and GSTT1 analyses were done with blood samples of prostate cancer patients and pseudo healthy individuals exposed to environmental pollutions. For this pilot study, a questionnaire was used to recruit 53 prostate cancer patients and 53 pseudo-healthy motorized bike drivers as well as matching healthy controls (already published elsewhere). Signed informed consent was collected before peripheral blood withdrawal in a 5 ml EDTA tube. DNA extraction was carried out in the laboratory with the phenol/chloroform method. The Multiplex polymerase chain reaction (PCR) was used to amplify and detect the presence of GSTM1 and GSTT1. Results: Our results showed that prostate cancer was more predominant in elderly men 60-80 years than 40-59 years (p <0.001), and the majority of cancer patients were uneducated (62%). We have also noticed that most of them were polygamous (78%) and reside in urban areas. No significant association was observed between the loss of GSTM1 or GSTT1 and prostate cancer. However, the combined losses of GSTM1 and GSTT1 showed a significant association with prostate cancer (P<0.05). However, we have noticed more deletion of GSTT1 in prostate cancer. Conclusion: Overall, our study determines that the impairment of GSTM1 and GSTT1 is associated with prostate cancer. Thus, the deficiency of GSTM1 and GSTT1 could be used as a predictive biomarker of predisposition to cancers including prostate
Keywords: Prostate; Cancer; Glutathione-S-transferases; detoxification; gene; multiplex PCR